2021
DOI: 10.3390/nano11020272
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Absorption and Adhesion Properties of Hydrophobic and Superhydrophobic Thermoset Epoxy Nanocomposite Coatings

Abstract: The enhancement of both thermal and mechanical properties of epoxy materials using nanomaterials becomes a target in coating of the steel to protect it from aggressive environmental conditions for a long time, with reducing the cost. In this respect, the adhesion properties of the epoxy with the steel surfaces, and its proper superhyrophobicity to repel the seawater humidity, can be optimized via addition of green nanoparticles (NPs). In-situ modification of silver (Ag) and calcium carbonate (CaCO3) NPs with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Indeed, it should be remarked that other approaches can be applied to form novel coatings in order to protect materials from corrosion, bacterial activity, and solvent impact, etc. Experiments and mathematical models have been shown in recently published papers [34][35][36][37][38][39][40][41][42][43] and have demonstrated their various advantages. However, the LOD technique has certain unique advantage that allows treatment of all types of the materials, such as inorganic crystals, semiconductors, metals, and some high-temperature polyimide structures, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it should be remarked that other approaches can be applied to form novel coatings in order to protect materials from corrosion, bacterial activity, and solvent impact, etc. Experiments and mathematical models have been shown in recently published papers [34][35][36][37][38][39][40][41][42][43] and have demonstrated their various advantages. However, the LOD technique has certain unique advantage that allows treatment of all types of the materials, such as inorganic crystals, semiconductors, metals, and some high-temperature polyimide structures, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, absorption and adhesion properties, as well as the hydrophobicity, etc. features should be taken into account [88]. Formation of the novel direction to study the structured materials used in the optoelectronics devices are important as well [89].…”
Section: Surface Relief Influence On the Physical-chemical Parameters...mentioning
confidence: 99%
“…In the alumina reinforced PSO/PDMS coat- In Figure 11, under the condition of 800-1400 rpm, the increase of alumina content and the decrease of particle size will decrease the drag reduction performance of the coatings. Some studies have shown that flexible materials have an obvious drag reduction effect, because the elastic modulus of the material is low, which can release friction resistance through surface deformation [34,35]. In the alumina reinforced PSO/PDMS coatings, the addition of alumina will increase the elastic modulus of the coatings, thus reducing the buffering effect of the coatings.…”
Section: Drag Reduction Performancementioning
confidence: 99%